Vaccine innovations for emerging infectious diseases—a symposium report. Issue 1 (28th October 2019) - Cable, Jennifer; Srikantiah, Padmini; Crowe, James E.; Pulendran, Bali; Hill, Adrian; Ginsberg, Ann; Koff, Wayne; Mathew, Anuja; Ng, Tony; Jansen, Kathrin; Glenn, Gregory; Permar, Sallie; et al.
Abstract: Vaccines have been incredibly successful at stemming the morbidity and mortality of infectious diseases worldwide. However, there are still no effective vaccines for many serious and potentially preventable infectious diseases. Advances in vaccine technology, including new delivery methods and adjuvants, as well as progress in systems biology and an increased understanding of the human immune system, hold the potential to address these issues. In addition, maternal immunization has opened an avenue to address infectious diseases in neonates and very young infants. This report summarizes the presentations from a 1‐day symposium at the New York Academy of Sciences entitled "Innovative Vaccines against Resistant Infectious Diseases and Emerging Threats, " held on May 20, 2019.